A Quasi-Experimental Study of the Effects of a Reciprocal Peer Coaching Strategy on Physiotherapy Students' Clinical Problem Solving Skills - Ladyshewsky, Richard Kaban (Curtin University, 2000)
This research was carried out to further the theoretical and practical understanding of peer assisted learning in undergraduate physiotherapy clinical education. A quasi-experimental study, with both a control group and an experimental group, was developed to examine the effects of peer assisted learning on the cognitive, psychomotor and affective components of clinical competence.On a more specific level, the main aim of the study was to investigate two models of clinical learning used in physiotherapy: the individualistic and reciprocal peer coaching models. Differences in history taking, physical examination and clinical reasoning were studied by having individual students, and pairs of students, complete an assessment of a simulated patient followed by a clinical reasoning test. A conceptual framework illustrates the main theoretical implications of this study. This framework incorporated current knowledge about clinical reasoning in medicine and the allied health sciences, in particular, reasoning from a novice practitioner's perspective. The conceptual framework, however, was expanded to demonstrate how peer assisted learning can influence the knowledge, cognitive and metacognitive aspects of clinical reasoning and performance.The main findings of the study were that reciprocal peer coaching led to statistically significant improvements in performance and clinical reasoning in the experimental group. In most cases, positive effect size differences appeared in favour of the experimental group. Most noteworthy differences were in the areas of physical examination and overall thoroughness of the patient encounter. Subjects in the experimental group also outperformed subjects in the control group on the overall clinical reasoning test to a statistically significant degree. A similar outcome was also noted in terms of patient management, that is, the planning and development of treatment interventions. Low achieving students in the reciprocal peer coaching group outperformed low achieving students who worked independently. Qualitative differences in the learning atmosphere of both models were also reported by subjects. While the actual clinical reasoning process did not appear to differ across both groups, practical differences in the actual learning experience did appear. Students in the experimental group reported being less anxious than students in the control group. The reciprocal peer coaching process was also an effective means of creating a supportive learning environment. These results are consistent with the major conclusions in the literature. Specifically, that peer assisted learning methods can increase achievement in learners (Goldschmid & Goldschmid, 1976; Johnson et al., 1998; Milson & Laatsch, 1996; Riggio et al., 1991; Riggio et al., 1994; Topping, 1996).